Acetabular Fractures in the Senior Population– Epidemiology, Mortality and Treatments - Firoozabadi, Reza (Arch Bone Jt Surg, 2017)
BACKGROUND: Management of acetabular fractures in the senior population can be one of the most challenging injuries to manage. Furthermore, treating surgeons have a paucity of information to guide the treatment in this patient population. THE PURPOSE OF THIS STUDY WAS TO DETERMINE: (1) demographic and epidemiologic data, (2) mortality rates for nonoperative compared to operative management at different time points, (3) common fracture configurations, and (4) fracture fixation strategies in senior patients treated with acetabular fractures. METHODS: Retrospective review of prospectively gathered data at a Level I trauma center over a five-year period. 1123 acetabular fractures were identified. 156 of them were for patients over the age of 65 (average age of 78). RESULTS: Falls and motor vehicle accidents accounted for the two most common mechanisms of injury. 82% of patients had significant medical comorbidities. 51 patients (33%) died within one year, in which 75% of them died within 90 days of their acetabular fracture. 84% of the deceased patients, i.e. from the group of 51 patients, had non-operative treatment. For patients treated with traction alone, there was a 79% one-year mortality and 50% mortality rate within 90 days. Within the entire cohort, 70% had either an associated both-column (ABC) or anterior column/posterior hemitransverse (AC/PHT) fracture pattern. Fifty-seven patients (36.5%) underwent open reduction and internal fixation using standard reduction techniques and surgical implants via two main surgical exposures of ilioinguinal (69%) and Kocher-Langenbeck (29%). CONCLUSION: Geriatric patients with acetabular fractures are uncommon accounting for only 14% of all acetabular fractures. Patients who undergo surgery show lower mortality rates. ABC and AC/PHT fracture patterns are the two most common fracture patterns. Routine fixation constructs and implants can be used to manage these challenging fractures. Most patients are unable to return to their homes and instead require skilled nursing facility during their convalescence.